The legal and economic aspects of the “Esports Illusion”—why competitive gaming fails to become an independent industry - Novák, Pál; Hohmann, Balázs; Sipos, Dávid; Szőke, Gergely (Frontiers in Sports and Active Living, 2025)
IntroductionThe esports industry has experienced rapid growth over the past decade; however, recent trends indicate a phase of consolidation rather than continued exponential expansion, often referred to as the “Esports Winter.” This paper examines the hypothesis that the lack of a coherent legal framework, combined with the industry's economic model and game publishers' dominance over esports competition rights, significantly influences the market correction and restructuring of the esports ecosystem.MethodsThis study employs a comparative legal analysis, focusing on intellectual property rights, contract law, and the regulatory asymmetries that define the esports ecosystem. Additionally, economic data from market reports and financial disclosures are used to examine the financial structures controlled by game publishers and to contextualize the industry's consolidation within the broader video game market.ResultsFindings reveal that the key factor in esports consolidation is the legal and economic dominance of game publishers, who retain full control over competition rights and financial structures. Unlike traditional sports, where governing bodies regulate commercial rights, esports remains publisher-driven, making independent growth and financial stability contingent upon their strategic priorities. While some esports ecosystems, such as those surrounding Counter-Strike 2 and Dota 2, allow for third-party tournament organization, the industry as a whole remains structurally dependent on game publishers. These companies, despite having the exclusive legal rights to esports competitions, are not primarily motivated to develop the industry beyond its function as a marketing and engagement tool for their games. Consequently, while publishers do not actively restrict independent esports growth, the lack of alternative legal frameworks prevents other stakeholders from establishing a broader, more autonomous regulatory structure. Moreover, esports revenues account for less than 1% of the global video game industry's total income, indicating that esports is a supplementary rather than a standalone sector.DiscussionThe study concludes that esports' current challenges stem from its integration within the video game industry rather than being an independent sports-like entity. The ongoing consolidation phase reflects a market correction rather than an existential crisis. Unlike traditional sports, esports lacks an overarching regulatory authority, as all competition rights remain within the control of game publishers. This structural characteristic is unlikely to change, given that intellectual property rights grant publishers exclusive authority over how their games are used in competitive settings.ConclusionRather than representing an industry-wide crisis, the current phase of esports reflects a long-term stabilization process in which it remains an extension of the broader video game market. While legal frameworks could theoretically alter the regulatory landscape, any fundamental shift would require game publishers to relinquish control over their intellectual property—an outcome that remains improbable. As a result, esports will likely continue to operate within publisher-driven economic models rather than evolving into an independent, traditionally governed sports industry.